O professor de educação especial nos Institutos Federais. - GUIMARÃES, Luciana (2021)
Special Education is transversal and is foreseen at all levels and teaching modalities, therefore, the presence of the special education teacher must be ensured as one of the actors of this modality. Once, the role of the school and its educators in the schooling of the target audience of Special Education is to effect accessibility, integrally, as school autonomy of diversity in all its manifestations. This research aims to analyze the role of Special Education teachers in Federal Institutes. Specifically: a) Outline the profile of the initial and continuing education of Special Education teachers; b) Describe the possibilities and challenges of the practice of Special Education teachers in research, extension and teaching; c) Describe the functionality and organization of the Specialized Educational Service; d) Analyze the conceptions about the institutional policy in the accessibility actions of the campus. This work consisted of an investigation of a descriptive character, following a qualitative approach, of the field study type, and had as participants 20 teachers in the area of Special Education from 11 Federal Institutes. Based on ethical procedures for research with human beings, the research was authorized under CAAE number: 3.927.464 by the Research Ethics Committee of the Federal University of São Carlos. For data collection, two instruments were used, a questionnaire and a script that was used for the interview, both carried out online. The registered data were treated and analyzed in light of the content analysis approach, and discussed with the scientific literature in the field of Education, Special Education, Political and Social Sciences. As a result, we found that the majority of respondents are graduates in Pedagogy with a postgraduate degree in Stricto Sensu in Education or Special Education programs. The employment relationship has a greater number of effective vacancies. The challenges in working with teaching, research and extension are the organization of the workload in the Individual Work Plan and the lack of human and material resources. Specialized Educational Service is prioritized in teaching, but it is not restricted to teaching activities, with the exception of three Special Education teachers. The completion of this study allowed describing the role of the Special Education teacher at Federal Institutes.